2018
DOI: 10.1371/journal.pone.0205985
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, treatment and control in Ghanaian population: Evidence from the Ghana demographic and health survey

Abstract: Hypertension is a major cause of cardiovascular disease morbidity and mortality in Ghana. This study examines the prevalence, awareness, treatment and control of hypertension among Ghanaian aged 15–49 years. This cross-sectional study retrieved data from the 2014 Ghana Demographic and Health Survey (GDHS). The sample, comprising of 13,247 respondents aged 15–49 years, was analysed using descriptive statistics, Chi-Square tests, independent sample t-tests and binary logistic regressions. The overall prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
108
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 45 publications
18
108
8
Order By: Relevance
“…is was generally more than the reports of other studies on the prevalence of hypertension. Sanuade et al [19] reported that the overall prevalence of hypertension in the Ghanaian population is 13.0%. Central to the prevalence of hypertension is International Journal of Hypertension population-based studies where individuals will independently indicate their status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…is was generally more than the reports of other studies on the prevalence of hypertension. Sanuade et al [19] reported that the overall prevalence of hypertension in the Ghanaian population is 13.0%. Central to the prevalence of hypertension is International Journal of Hypertension population-based studies where individuals will independently indicate their status.…”
Section: Discussionmentioning
confidence: 99%
“…Ahoe has a population size of 1,234 [16] and has limited access routes and community facilities. Hypertension is one of the top three leading causes of all deaths and among the top ten reasons for outpatient attendance in the Volta regional [19] and the Ho municipal hospitals. e Ho teaching hospital (formally called the Volta regional hospital) and the Ho municipal hospitals principally serve the Ahoe and adjourning periurban communities.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported rates of 32.9%-49%among similar population groups (2,(14)(15)(16). In Ghana, however, control rates reported are relatively lower and range from 24% to 42% (17)(18)(19). The available studies that have established the high prevalence of uncontrolled hypertension in Ghana, but found inconsistent associations between socio-demographic factors and blood pressure control (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, however, control rates reported are relatively lower and range from 24% to 42% (17)(18)(19). The available studies that have established the high prevalence of uncontrolled hypertension in Ghana, but found inconsistent associations between socio-demographic factors and blood pressure control (18,19). Where client level factors have been assessed, evidence shows poor control associated with the number of hypertensive medications, duration of diagnosis and access to medication (19).…”
Section: Introductionmentioning
confidence: 99%